NON PERFORMING LOAN SEBAGAI PEMODERASI PENGARUH KUR PADA PROFITABILITAS PT BRI (PERSERO) TBK CABANG DENPASAR - Gladys, Loranita; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 20 No 1 (2017), 2017)
This r esearch has using purposive sampling method of determining the purpose of obtaining a representative sample in accordance with the specified criteria. Data were collected by Library Research and Field Research, by using Moderated Regression Analysis as a data analysis technique. The analysis showed that in partial KUR positive and significant have impact ed on profitability. Moderate variable which is the interaction between the KUR and NPL found to be significant (sig <0.05) so it can be concluded that the NPL is a variable moderating variables that are weakening the people's business credit relationship with profitability at PT.Bank Rakyat Indonesia (Persero) Tbk.
Keywords: Business credit (KUR), Profitability, Non Performing Loan